A Remarkable Reductive Dearomatization of Thiophene and Furan Rings - Nguyen, Son T.; Ding, Xiaoyuan; Peet, Norton P. (Synthesis, 2013)
Reduction of a 2-nitrothiophene 4 and the corresponding 2-nitrofuran 20 with zinc and acetic acid produced a remarkable dearomatization and fragmentation reaction to give acyclic nitriles 6 and 22, respectively. The intermediate 2-aminothiophene 5 was trapped by acylation with acetic anhydride to give acetamide 7. An additional acrylonitrile intermediate 17 was also trapped by Michael addition with benzyl mercaptan to give adduct 18. An alternate synthesis of nitrile 22 produced in the reduction of nitrofuran 20 provided an authentic sample of the product. The conversion of nitroaromatic heterocycles 4 and 20 into aliphatic nitriles 6 and 22 are remarkable and unprecedented reactions.
Keywords: thiophene; furan; zinc; furazolidone; nitrofurantoin; reductive dearomatization